A new species of Paratanakia (Teleostei: Cyprinidae) from Guangdong, China - Huang, Shih-Pin; Cheng, You-Hua; Shao, Kwang-Tsao; Chen, I-Shiung (Zootaxa, 2024)
A new species of bitterling, Paratanakia haifengensis sp. nov. was collected from Guangdong Province in southern China is described in this study. P. haifengensis sp. nov. can be well distinguished from P. himantegus (Günther, 1868) and P. chii (Miao, 1934) based on the following morphological characters: (1) meristic counts: dorsal fin rays 3, 9; anal fin rays modally 3, 12; pectoral fin rays modally 1, 13; lateral-line scales modally 36; (2) specific longitudinal blue stripe on body side: the longitudinal blue stripe extending forward to the position below the third spine of dorsal fin in maximum and usually not exceeding the anterior margin of dorsal fin, its anterior tip inserted above the 13th–14th lateral-line scales; and (3) specific dorsal fin color pattern: dorsal fin with a broad shiny yellow stripe, and with an indistinct, very thin gray margin in male. In this study, the coloration, morphometric measurements and meristic features of P. haifengensis sp. nov. will be provided and the comparison of morphological characters between P. haifengensis sp. nov. and other species of Paratanakia will be discussed. In addition, a diagnostic key to all species of Paratanakia will be provided in this paper.